Comparative Analysis of Sleep Quality between Medical and Nonmedical Students at Gulu University, Uganda - Brenda Nakitto; Federes Nansubuga; Edward Omondi; Moses Opedo; Felix Bongomin (Journal of Public Health and Primary Care)
Background: Adequate sleep is essential for overall health and well-being, and poor sleep quality significantly affects academic performance. In this study, we evaluated and compared the quality of sleep among medical and nonmedical students at Gulu University in Uganda. Methods: We conducted a cross-sectional study recruiting undergraduate students of Gulu University, Gulu, Uganda. Data were collected using self-administered questionnaires. Pittsburgh Sleep Quality Index (PSQI) and Patient Health Questionnaire-9 (PHQ-9) were used to assess sleep quality and depression, respectively. PSQI score >5 defined poor sleep quality and PHQ-9 score ≥5 depression. Multivariable logistic regression analysis was used to identify independent predictors of poor sleep quality. P <0.05 was considered statistically significant. Results: Of the 513 participants enrolled, 199 (38.8%) were female, with a median age of 23 (interquartile range: 22–25) years. Overall, 395 (77.0%) students had poor sleep quality (nonmedical students 317 [80.3%] vs. medical students 78 [19.8%], P = 0.023). The prevalence of symptoms of depression was 57.7% (n = 296) and was significantly higher among those with poor sleep quality compared to those with good sleep quality (259 [65.6%] vs. 37 [31.4%], P < 0.001). The odds of having poor sleep quality were over 4-fold higher among students with symptoms of depression than those without (adjusted odds ratio: 4.31, 95% confidence interval: 2.45–7.60, P < 0.001). Conclusions: The study findings reveal a high prevalence of poor sleep quality and depression among students at Gulu University. Routine screening of sleep quality and depressive symptoms is necessary to control and prevent their impact on the performance and well-being of university students.